Analisis Peranan Work Life Balance dalam Pengukuran Kinerja Karyawan pada PT Karya Visual Anantara Jakarta Barat - Andhika Prameswara; Rahmat Subur (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to analyze the implementation of Work Life Balance and its impact on employee performance at PT Karya Visual Anantara, located in West Jakarta. As part of the creative industry, the company operates in a fast-paced environment with high client expectations and frequent revisions, making work–life balance a critical factor in maintaining employee well-being and performance. This research employs a qualitative case study approach using in-depth interviews, observations, documentation, and Focus Group Discussions (FGD) involving key informants such as the director, finance staff, and editors. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing, supported by validity testing through credibility, transferability, dependability, and confirmability. The findings indicate that flexible working hours, supervisor support, and a family-oriented work culture serve as internal strengths that positively influence employee performance. The implementation of Work From Home (WFH) and adjustable working schedules allows employees to maintain focus, manage emotional well-being, and improve productivity. However, several weaknesses were identified, including misalignment between workload and personal time, increased pressure during critical periods, and communication issues with clients. SWOT analysis shows that both the IFAS and EFAS scores are 2.2, placing the company in Quadrant II (Stable – Maintain Strategy). This position suggests that the organization must maintain its existing strategies while enhancing time management, cross-department communication, and workload distribution. Overall, the study concludes that Work Life Balance contributes positively to employee performance, yet continuous improvement is required to optimize its long-term implementation within the organization.